Memorandum of Understanding between the International Livestock Research Institute (ILRI) and Debre Tabor University - International Livestock Research Institute; Debre Tabor University (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
Memorandum of understanding (MOU) between the International Livestock Research Institute (ILRI) and Debre Tabor University. On March 31, 2022, MoU was signed by Jimmy Smith, Director-General of ILRI, and Anegagergn Gashaw, President of Debre Tabor University.